Thomas Carlyle and Stoicism. (10th October 2020) - Jordan, Alexander
Abstract: Recent studies have pointed to the importance of Thomas Carlyle's engagement with classical thought, especially Epicureanism and Cynicism. However, in these recent studies, Carlyle's debts to Stoicism have received only passing attention. Previous scholars hardly considered the question at all, and those who did argued that Carlyle could never have accepted the passive withdrawal and indifference of the Stoics. By way of corrective, the current article offers a comprehensive account of Carlyle's engagement with Stoicism, showing that he subscribed to an active interpretation of the latter that emphasized will, duty, and heroic action. Indeed, contemporaries were well aware of Carlyle's debts to Stoicism, pointing out that his thought stood in stark contradiction to Christian doctrines of original sin. Thus, while Carlyle's Stoicism was compatible with his hereditary Calvinism insofar as divine providence and duty were concerned, there was a significant contradiction regarding the question of sin. In this sense, Carlyle's Stoicism made an important contribution to the 'meliorist' revolt against orthodox Christianity.